2023
DOI: 10.3389/fpubh.2023.1248462
|View full text |Cite
|
Sign up to set email alerts
|

Social interaction trajectories and all-cause mortality in older adults: the Otassha study

Hisashi Kawai,
Manami Ejiri,
Kumiko Ito
et al.

Abstract: IntroductionThis longitudinal study aimed to identify aging trajectory patterns of social interaction by sex and determine the association between these patterns and all-cause mortality.MethodsParticipants were 4,065 community-dwelling older adults (1849 men) in Japan, aged 65–89 years, who responded twice or more to a mail survey conducted between 2012 and 2020. Social interaction was examined through the frequency of face-to-face and non-face-to-face contact with non-resident family and friends. The aging tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A previous study reported that social function declines more slowly than physical function [ 26 ]. Our previous study suggested that social interaction is maintained in old age [ 15 ]. However, regarding the pattern of the rapid decline in SR, the SR question on the TMIG-IC could have included awareness of the social support provided, such as being called on for advice, visiting sick friends, and initiating conversations with young people.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study reported that social function declines more slowly than physical function [ 26 ]. Our previous study suggested that social interaction is maintained in old age [ 15 ]. However, regarding the pattern of the rapid decline in SR, the SR question on the TMIG-IC could have included awareness of the social support provided, such as being called on for advice, visiting sick friends, and initiating conversations with young people.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up mail surveys were conducted in October 2013, 2014, 2017, 2018, 2019, 2020, 2021, and 2022. The mail survey for this cohort was published elsewhere [ 2 , 14 , 15 ]. The mail survey for this cohort includes a space to indicate whether the person is completing the survey independently or if a family member completed it for them.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation